2022
DOI: 10.1038/s41467-022-33444-0
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox cooperative N-heterocyclic carbene/palladium-catalysed alkylacylation of alkenes

Abstract: Three-component carboacylation of simple alkenes with readily available reagents is challenging. Transition metal-catalysed intermolecular carboacylation works for alkenes with strained ring or directing groups. Herein, we develop a photoredox cooperative N-heterocyclic carbene/Pd-catalysed alkylacylation of simple alkenes with aldehydes and unactivated alkyl halides to provide ketones in good yields. This multicomponent coupling reaction features a wide scope of alkenes, broad functional group compatibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…During the preparation of this manuscript, Houk and Zhao et al reported the NHC-catalyzed aminoacylation of alkenes tethered with O -aryl oxime . Inspired by the efficient generation of iminyl radicals from readily available α-imino-oxy acids and our ongoing interests in alkene 1,2-difunctionalizations and NHC catalysis via radicals, , we envisioned that the reaction of alkene-tethered α-imino-oxy acids, with acyl imidazoles under photoredox NHC catalysis, might be feasible to deliver the corresponding N-heterocyclic molecules via the N-radical and ketyl radical (Scheme c). The alkene-tethered α-imino-oxy acids could be easily prepared via condensation of the corresponding enones with α-amino-oxy acid.…”
mentioning
confidence: 99%
“…During the preparation of this manuscript, Houk and Zhao et al reported the NHC-catalyzed aminoacylation of alkenes tethered with O -aryl oxime . Inspired by the efficient generation of iminyl radicals from readily available α-imino-oxy acids and our ongoing interests in alkene 1,2-difunctionalizations and NHC catalysis via radicals, , we envisioned that the reaction of alkene-tethered α-imino-oxy acids, with acyl imidazoles under photoredox NHC catalysis, might be feasible to deliver the corresponding N-heterocyclic molecules via the N-radical and ketyl radical (Scheme c). The alkene-tethered α-imino-oxy acids could be easily prepared via condensation of the corresponding enones with α-amino-oxy acid.…”
mentioning
confidence: 99%
“…In addition to ionic-type (2-electron) mechanisms, thiazol-2-ylidenes have also recently become privileged organocatalysts for radical transformations of aldehydes. In these reactions, the Breslow-type enolates C – , which result from the condensation of aldehydes with NHCs in basic conditions, are able to undergo spontaneous single-electron transfer (SET) to challenging substrates ( E ox > −1.6 V vs SCE). In the absence of aldehydes, free NHCs are milder reducing reactants. For instance, imidazol-2-ylidenes perform stoichiometric reduction of the ferrocenium cation ( E = +0.38 V vs SCE) and the trityl cation ( E = +0.27 V vs SCE) .…”
mentioning
confidence: 99%
“…Recently N-heterocyclic carbene (NHC)-catalyzed radical cross-coupling reactions provide an novel method to give diverse ketone compounds . Using a myriad of C­(sp 3 )-centered radical precursors such as N -hydroxyphthalimide (NHPI) ester, Hantzsch ester, Katritzky pyridinium salt, and others, a C­(sp 2 )–C­(sp 3 ) bond can be efficiently constructed (Scheme b). Despite much progress, the direct cross-coupling between NHC-derived ketyl radicals and C­(sp 2 )-centered radicals to form C­(sp 2 )–C­(sp 2 ) bonds remains elusive.…”
mentioning
confidence: 99%